Uma formalização da mecânica clássica dos corpos rígidos - Martins, Luiz Carlos (1970)
We considera formalization of the rational mechanics of a rigid body under a intrinsic viewpoint. Only elementary concepts of bilinear algebra and measure theory are used. We restrict ourselves to the problems of the determination of the required forces to produce and sustain any well-behaved motion of a given rigid body and then suggest a interpretation for the resolution. of the reciprocal problem. Kinematics is completely reduced to linear algebra. The existence of the angular velocity vector then follows from the representation of the linear part of the derivative of a one-parmeter family of isometries, in opposition to the usual heuristic form in which such vector is commonly introduced.